A bolt defect detection method for transmission lines based on improved YOLOv5 - Zou, Hongbo; Sun, Jialun; Ye, Ziyong; Yang, Jinlong; Yang, Changhua; Li, Fengyang; Xiong, Li (Frontiers in Energy Research, 2024)
To solve the problem of bolt defects in unmanned aerial vehicle (UAV) inspection that are difficult to identify quickly and accurately, this paper proposes a defect detection method based on the improved YOLOv5 anchor mechanism. Firstly, the Normalized Wasserstein distance (NWD) evaluation metric and the Intersection over Union (IoU) evaluation metric are combined, and the experiment determines the appropriate weight for this combination. This way, the sensitivity of using IoU alone to small objecet detection anchor box threshold changes was reduced. Furthermore, Convolutional Block Attention Module (CBAM) is included into the head network architecture of YOLOv5 in order to prioritize significant information and suppress irrelevant features. Omni-dimensional Dynamic Convolution (ODConv) is used to replace convolution in MobileNetv2.The combination module is used as the new backbone of the YOLOv5 model. It simultaneously enhances the model's capability to extract bolt defect object information, minimizes calculation requirements, and achieves lightweight detection across the entire model. Compared with the original algorithm, the model detection Accuracy Precision (AP) is increased by 30.1%, the mean Accuracy Precision (mAP) is increased by 30.4%. Other evaluation metrics of the model, such as GFlOPs and Parameters, all decreased slightly. The above results show that the improved algorithm proposed in this paper greatly improves the detection accuracy of the model on the premise of ensuring that the model is as small as possible.